China-Pakistan Economic Corridor: A Rational Choice Theory Perspective - Ali, Tayyaba Zainab; Askari, Muhammad Usman (Annals of Human and Social Sciences, 2023)
China and Pakistan have a long history of bilateral diplomatic, economic, and military relations. China’s economic assistance to Pakistan has a background of decades. CPEC is a project of the BRI initiative. The core interests of both China and Pakistan are attached to CPEC. In this global village connectivity is the core concern of any state to become prosperous and advanced. The essential purpose of this study was to explore the cost-benefit relations arising from CPEC. This bilateral project is analyzed under the lens of rational choice theory, and how China and Pakistan, as rational actors, took CPEC initiatives with maximum benefits and minimum losses is studied under this theoretical lens. This study was conducted using qualitative research methodology with primary and secondary source data. Three approaches of qualitative research methodology were incorporated to find answers to the research questions. Newspapers, official statements, think tanks, official websites, government documents, journal articles, research papers, books, and previous studies were used as data sources. Document analysis by Scott was used for data analysis and to measure the originality and authenticity of the collected data. This study raises awareness of the adverse effects of CPEC on the natural environment of Pakistan. This study analyzes the current scenario of CPEC and its potential impacts on the natural environment and determines the threats associated with CPEC developments on environmental attributes. CO2 and GHG emissions harm the environment and negatively impact public health. The fundamental aim of the CPEC is to mitigate the energy crisis despite all these harms, and Pakistan still faces an energy shortage.